The Automated Process Control Model for Energy Consumption Optimization within Plantain Flour Processing Facility - ADEYERI, Michael Kanisuru; AYODEJI, Sesan Peter; OLUTOMILOLA, Emmanuel Olatunji; ABAYOMI, Oluwatayo Johnson (International Journal of Industrial Engineering and Management, 2022)
Energy usage is a great concern for industrialists because it is a prime determinant of production cost. When energy consumption becomes a challenge, the industrial production process remains unsustainable. Hence, the need for automating the process control model of the plantain flour processing facility for its energy consumption optimization. Time and motion study was used on the plantain processing plant on a modular basis to develop the control system. The model control system for the plant was simulated and implemented. Experimental runs were carried out, and a system response time of 30 milliseconds was computed. In comparison, the results show that using the automated facility saved 30% more energy than running the plant manually. Thus, contributing control process model as an energy optimization concept for plantain flour plant facility. Article history: Received (March 3, 2022); Revised (August 9, 2022); Accepted (August 26, 2022); Published online (August 30, 2022)